Revised Swedish guidelines on intravenous iodine contrast medium-induced acute kidney injury 2022: A summary. (May 2023) - Nyman, Ulf; Brismar, Torkel; Carlqvist, Jeanette; Hellström, Mikael; Lindblom, Maria; Lidén, Mats; Liss, Per; Sterner, Gunnar; Wikner, Franciska; Leander, Peter
The Swedish Society of Uroradiology has revised their computed tomography (CT) guidelines regarding iodine contrast media-induced acute kidney injury (CI-AKI). They are more cautious compared to the European Society of Urogenital Radiology and the American College of Radiology since the actual risk of CI-AKI remains uncertain in patients with moderate to severe kidney damage due to a lack of prospective controlled studies and mainly based on retrospective propensity score-matched studies with low-grade evidence. Another source of uncertainty is the imprecision of glomerular filtration rate (GFR) estimating equations. However, randomized hydration studies indictae an upper limit risk of CI-AKI of about 5% for outpatients with a GFR in the range of 30–44 or 45–59 mL/min/1.73m 2 combined with multiple risk factors. Apart from GFR limits, the guideline also includes limits for systemic contrast medium exposure expressed in gram-iodine/GFR ratio.